Selecting Educational Resources - Tyler D'Angelo; Debra Barry; James C. Bunch; Andrew C. Thoron (EDIS)
Many instructors struggle to find appropriate educational resources. However, collaborative teaching and learning efforts have created a number of educational resources that can be stored, shared, adapted, and used within the agricultural education profession. This 7-page document will help educators in selecting educational resources. Written by Tyler D’Angelo, Deb Barry, J. C. Bunch, and Andrew Thoron and published by the UF/IFAS Department of Agricultural Education and Communication, June 2018. http://edis.ifas.ufl.edu/wc303